Antibacterial activity of carbon nanomaterials - Liu, Shaobin (2012)
Carbon nanomaterials (CNMs), including graphene based materials, carbon nanotubes and fullerene, have been intensively studied in recent years because of their unique properties and various potential applications. This thesis focuses on the antibacterial activity of CNMs, more specifically, one-dimensional single walled carbon nanotubes (SWCNTs) and two dimensional graphene based materials, including graphite (Gt), graphite oxide (GtO), graphene oxide (GO), and reduced graphene oxide (rGO).